The Influence Of Organic Matter Of Kirinyuh (Eupathorium Odoratum) and That Of Organic Matter Of Paitan (Tithonia Diversifolia) On Some Soil Chemical Properties and Maize Yield On Ultisols - Andreas Napitupulu; Posma Marbun; Supriadi Supriadi (Universitas Sumatera Utara, 2018)
The study was performed in order to investigate the influence of organic matter of kirinyuh (Eupathorium odoratum) and that of organic matter of paitan (Tithonia diversifolia) on some soil chemical properties and maize yield on Ultisols of Village Huta Ginjang. The experiment was in a non-factorial randomized complete block design. The treatments included control, inorganic NPK 100 %, fresh bitter bush 10 t/ha, fresh wild sunflower 10 t/ha, decayed bitter bush 10 ton/ha, decayed wild sunflower 10 ton/ha, fresh bitter bush 10 ton/ha + 50 % NPK, fresh wild sunflower 10 ton/ha + 50 % NPK, decayed bitter bush 10 ton/ha + 50 % NPK, and decayed wild sunflower 10 ton/ha + 50 % NPK. The treatments was replicated three times. The results showed that the applications of fresh bitter bush (Euphatorium odoratum), decayed bitter bush, fresh bitter bush + 50 % NPK and fresh wild sunflower (Tithonia diversifolia), decayed wild sunflower, fresh wild sunflower + 50 % NPK significantly increased soil pH, N-total of soil, exchangeable K of soil, fresh fruit weight, and the 1,000 maize seed weight. However, the application of decayed wild sunflower combined with NPK was the most appropriate one since it generated the extraordinary value on parameters: soil pH, exchangeable K, fresh fruit weight and the 1,000 maize seed weight with their values in turn: 5,41; 2,53 me/100g; 357,33 g/plot dan 303,33 g/plot. Keywords :kirinyuh, maize production, organic matter, tithonia, Ultisol